Analisa yuridis tindak pidana kekerasan dalam rumah tangga (studi putusan: no.237/Pid.B/2009/PN Sleman, no.60/Pid/2009/Pty, no.302k/Pid.Sus/2010 - Fauzizah Hanum (Fak. Syariah dan Hukum UIN Sunan Kalijaga, 2014)
ir, rt